Synchronous Ovarian and Endometrial Endometrioid Adenocarcinoma Presenting with Nonbacterial Thrombotic Endocarditis and Pulmonary Thromboembolism: Adenocarcinoma with Thrombotic Events. (21st October 2015) - Erturk, N. K.; Erturk, A.; Basaran, D.; Ozgul, N.
Abstract : Introduction. Nonbacterial thrombotic endocarditis (NBTE) is a rare manifestation of hypercoagulability in patients with malignant neoplasms. Case Report. A fifty-six-year-old woman presented to the emergency service; the clinical workup revealed deep vein thrombosis in right leg and bilateral massive PTE. As the abdominal sections on the spiral CT revealed a giant pelvic mass of ovarian origin, she was referred to our hospital's gynecologic oncology department. She was scheduled for surgery under enoxaparin. She described numbness on one side of her face. Cranial imaging findings revealed acute ischemic cerebral lesions and transesophageal echocardiogram showed vegetation on the aortic cusp. Under anticoagulation treatment, she underwent hysterectomy with bilateral salpingo-oophorectomy and infracolic omentectomy. After tumor resection, her neurological symptoms dissolved with aggressive anticoagulant treatment. Pathology result was synchronous endometrial and ovarian adenocarcinoma. Discussion. NBTE is a rare condition often associated with advanced malignancies. Peripheral embolism and venous thrombosis are complications that have been associated with NBTE due to hypercoagulable state. These disorders could be resistant to routine anticoagulant treatment. In case of a thrombotic complication due to ovarian malignancy, surgical resection of the primary tumor may increase the effect of anticoagulant treatment.